A revised concept of Rhipidoglossum (Angraecinae, Orchidaceae) - Farminhão, João N. M.; Meerts, Pierre; Descourvières, Pascal; Droissart, Vincent; Simo-Droissart, Murielle; Stévart, Tariq (Phytotaxa, 2018)
Following the production of a near-comprehensive generic phylogenetic analysis of African angraecoid orchids, paraphyly of the genus Rhipidoglossum relative to Cribbia, Margelliantha and Rhaesteria was in need of being resolved by integrating morphological observations into this newly available molecular framework. Accordingly, we critically revised the diagnostic traits of each genus by examining about 700 herbarium specimens ascribable to 50 species of Rhipidoglossum and its satellite genera. Cribbia, Margelliantha and Rhaesteria are here lumped with Rhipidoglossum, along with Angraecopsis pusilla and Diaphananthe millarii. The presence of pollinaria with two separate disk-shaped viscidia, a trilobed, non-papillate rostellum with midlobe more prominent than lateral lobes and an undivided lip are diagnostic of this more inclusive concept of Rhipidoglossum. In line with this new taxonomic arrangement, 11 new combinations in Rhipidoglossum are made, and Margelliantha lebelii is moved to Diaphananthe and first reported for Uganda.